A truncated peptide Spgillcin177–189 derived from mud crab Scylla paramamosain exerting multiple antibacterial activities - Wang, Xiaofei; Hong, Xiao; Chen, Fangyi; Wang, Ke-Jian (Frontiers in Cellular and Infection Microbiology, 2022)
Antimicrobial peptides (AMPs) may be the most promising substitute for antibiotics due to their effective bactericidal activity and multiple antimicrobial modes against pathogenic bacteria. In this study, a new functional gene named Spgillcin was identified in Scylla paramamosain, which encoded 216 amino acids of mature peptide. In vivo, Spgillcin was dominantly expressed in gills of male and female crabs, offering the highest expression level among all tested organs or tissues. The expression pattern of Spgillcin was significantly altered when challenged by Staphylococcus aureus, indicating a positive immune response. In vitro, a functional truncated peptide Spgillcin177-189 derived from the amino acid sequence of Spgillcin was synthesized and showed a broad-spectrum and potent antibacterial activity against several bacterial strains, including clinical isolates of multidrug-resistant (MDR) strains, with a range of minimum inhibitory concentrations (MICs) from 1.5 to 48 μM. Spgillcin177-189 also showed rapid bactericidal kinetics for S. aureus and Pseudomonas aeruginosa, but did not display any cytotoxicity to mammalian cells and maintained its antimicrobial activity in different conditions. Mechanistic studies indicated that Spgillcin177-189 was mainly involved in disruption of cell membrane integrity where the membrane component lipoteichoic acid (LTA) and lipopolysaccharide (LPS) could significantly inhibit the antimicrobial activity in a dose-dependent manner. in iddition, Spgillcin177-189 could change membrane permeability，caused accumulation of intracellular reactive oxygen species (ROS) and ultimately resulted in cell death. No resistance was generated to Spgillcin177-189 when the clinical isolates of MRSA and MDR P. aeruginosa were treated with Spgillcin177-189, and then subjected to long term of continuous culturing for 50 days. In addition, Spgillcin177-189 exerted strong anti-biofilm activity by inhibiting biofilm formation, and was also effective at killing extracellular S. aureus in the cultural supernatant of RAW 264.7 cells without inducing apoptosis. Taken together, Spgillcin177-189 has strong potential as a substitute for antibiotics in future aquaculture and medical applications.